Presidential addresses and state papers, Volume 2 (of 7) - Roosevelt, Theodore, 1858-1919 (Salt Lake City, UT : Project Gutenberg, 2024)
"Presidential Addresses and State Papers, Volume 2" by Theodore Roosevelt is a collection of political speeches and writings delivered during the presidency of Roosevelt in the early 20th century. The work encompasses his addresses from December 3, 1901, to January 4, 1904, and serves as a reflection of the principles and policies he championed during this period. The topics range from the importance of a strong navy to the responsibilities of citizenship and the moral obligations that accompany education. The beginning of the volume features dedications of notable monuments, such as the Navy Memorial in San Francisco, where Roosevelt emphasized the significance of military preparedness. He called for ongoing investment in the navy to ensure national security, highlighting the principle that successful military campaigns rely heavily on prior preparation. Roosevelt also addressed audiences at the University of California, stressing the critical relationship between education and civic duty, urging graduates to be responsible citizens. His rhetorical style combines a call to action with a reflection on the nation$1 (Bs history, utilizing personal anecdotes to illustrate broader themes of duty, citizenship, and national pride. (This is an automatically generated summary.)s
Release date is 2024-11-05
A Marshall and The Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Roosevelt, Theodore, 1858-1919; United States -- Politics and government -- 1901-1909